Effectiveness of the Jemput Bola Program at the Population and Civil Regis-tration Service of Jeneponto Regency - Maharani, Muh. Ilham Adhythama; Ahmad, Badu (IHSA Institute, 2024)
The Integrated Pickup Program is a public service innovation carried out by the Jeneponto Regency Population and Civil Registry Office as an effort to accelerate services in order to reach all people of Jeneponto Regency to get easy and fast services to take care of population document ownership. The target of this Integrated Pickup Program is all villages in Jeneponto Regency, the main focus of this Integrated Pickup Program is villages that still have a low percentage of population document ownership. The research method in this study uses a qualitative approach that explains objects according to the facts that occur in the field, this type of research uses a descriptive type that shows a picture of what happens in the field based on facts in the field. In addition, the purpose of the Integrated Pickup Program is to provide knowledge about the importance of recording population events. With this, the purpose of this study is to determine how effective the Integrated Pickup Program is which is analyzed using Duncan's effectiveness theory quoted by Richard M. Steers (1985:53) which includes, 1) achievement of goals, 2) integration, 3) adaptation.